Gaseous mercury capture by coir fibre coated with a metal-halide. (2nd July 2020) - McCarthy, Damien N.; Edwards, Grant C.
ABSTRACT: Toxic gaseous elemental mercury (GEM) is emitted to the atmosphere through a variety of routes at rates estimated at over 5000 tonnes per annum, a large fraction of which is Anthropogenic. It is then widely disbursed atmospherically and eventually deposited, where it is subject to further biogeochemical cycling, including re-emission. Research into capture of point source mercury emissions revolves almost exclusively around the use of activated carbons, various catalytic oxidation substrates, or as a by-product of acidic treatments of flue gas during SOx and NOx reduction methods. GEM is very non-reactive in its native state, but capture rates are greatly enhanced if GEM is first oxidized, or at least where oxidation states play a role at the substrate GEM interface. Little research has been devoted to capture of GEM directly. However, presented here is a novel adaption of coir fibers for use as a substrate in capturing GEM emissions directly. Various coir modifications were investigated, with the most effective being fibers coated with CuI crystals dispersed in a non-crosslinked poly-siloxane matrix. Scanning electron microscopy was used to view surface morphologies, and sorption characteristics were measured using atomic absorption spectroscopy (AAS). These results indicate that coir fibers modified by CuI-[SiO2 ] n show great promise in their ability to efficiently sorb GEM, and could potentially be utilized in a variety of configurations and settings where GEM emissions need to be captured. Implications: Highly toxic gaseous elemental mercury (GEM) has proved very difficult to capture, requiring complex catalytic oxidation or expensive gas scrubbing technologies. The modified coir fiber described in this work can effectively capture GEM without prior catalytic oxidation or any other physicochemical treatment of the gas. The solution provided here is made from renewable resources, is low cost, and the raw materials are readily available in bulk. Further, the mercury is bound in a stable and insoluble form that can be readily isolated from the substrate. This filtration device can be adapted to suit a variety of settings for GEM capture.